Ekonomi Islam dan Keadilan Sosial dalam Implementasi Sistem Ekonomi Syariah Mengurangi Ketimpangan Sosial di Negara Berkembang: Tinjauan Sistematis - Ekawaty, Marlina; Jumiyanti, Kalzum (el-Jizya : Jurnal Ekonomi Islam, 2025)
Social inequality in developing countries remains a major challenge despite various economic interventions that have been made. This study aims to evaluate the role of Islamic economic systems in promoting social justice and reducing social inequality through a systematic review approach. This study uses the Systematic Literature Review (SLR) method for scientific publications for the period 2020–2025, with thematic analysis and visualization techniques using VOSviewer. The results of the study show that Islamic economic instruments such as zakat, waqf, and infaq have a significant contribution to wealth redistribution, community empowerment, and the achievement of the Sustainable Development Goals (SDGs). The findings indicate that the application of Islamic economics is effective in reducing inequality if supported by good governance and inclusive policies. This research confirms the importance of value-based economic systems for social justice and encourages follow-up studies that empirically test the effectiveness of Islamic economic implementation in various local contexts.